TEACHER AS A ROLE MODEL IN THE 2013 CURRICULUM DEVELOPMENT - Fithriani Fithriani; Syabuddin Syabuddin; Gunawan Gunawan; T. Zainuddin; Sulaiman Sulaiman (Universitas Islam Negeri Ar-Raniry, 2021)
The importance of the teachers as role models for students is related to their personality to build the character of students. Character education can be carried out through existing programs in schools, such as integrating it in learning and implementing it through extracurricular activities. In addition, the curriculum influences all educational activities; without a curriculum, the learning process will not work well. In this case, the role of the teachers is not only to educate students following the curriculum demands but also to provide an example to students by becoming individual role models. Teachers who become role models will be able to show attitudes and behaviour following values and norms in daily life so that students can see and imitate them. Teacher as a role model will support the character education program and help students to have good character